International Architecture News - Grigorieva, Anna (project baikal, 2026)
The news section presents the laureate of the 2026 Pritzker Architecture Prize, theresults of the international student ideas competition Catalysts of Resilience andThe Architecture MasterPrize 2025. It also announces the new edition of the KairaLooro 2026 Competition.
Keywords: Internation Union of Architects; Pritzker Architecture Prize; international student ideas competition; The Architecture MasterPrize; Kaira Looro Competition